2021
DOI: 10.1111/bjc.12334
|View full text |Cite
|
Sign up to set email alerts
|

Italian adolescents’ adjustment before and during the coronavirus disease 2019: A comparison between mothers’ and adolescents’ perception

Abstract: The current cross‐sectional study aimed to analyse adolescents’ adjustment during and before the lockdown caused by the coronavirus disease 2019 pandemic, by evaluating levels of emotional problems and hyperactivity as referred by adolescents themselves. A further purpose was to compare adolescents’ and mothers’ perception about adolescents’ adjustment. Participants comprised 206 adolescents (50.5% females; mean age = 12.2; SD = 3.3) and their mothers (mean age = 43.9; SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…Moreover, in the evaluation of the complexity of factors that may be entangled in the onset of IA, future studies should also include the evaluation of the relationship with peers, which is particularly salient in this period of the life cycle. Finally, this study was carried out before the beginning of the COVID-19 pandemic and therefore it does not take into consideration the huge changes that the pandemic has produced on parent–child relationships [ 87 , 88 , 89 ] and Internet addiction [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the evaluation of the complexity of factors that may be entangled in the onset of IA, future studies should also include the evaluation of the relationship with peers, which is particularly salient in this period of the life cycle. Finally, this study was carried out before the beginning of the COVID-19 pandemic and therefore it does not take into consideration the huge changes that the pandemic has produced on parent–child relationships [ 87 , 88 , 89 ] and Internet addiction [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that we have not assessed the children’s experience from their own point of view. A recent study found a high consistency between mothers’ and children’s perceptions of children’s psychological adjustment (Babore et al, 2021a ); however, future research could further explore if the parents’ perception matches with the actual psychological status of the children. Another limitation regards the unbalanced representation of both parents as most participants comprised mothers.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies with other clinical pediatric populations, as children with developmental disorders, found increased levels of children’s emotional and behavioral difficulties (Conti et al, 2020 ). Studies among healthy children detected negative psychological outcomes during COVID-19 emergency (Babore et al, 2021a , b ; Wang et al, 2020 ). Some measures implemented to avoid the spread of the virus (such as social isolation, the closure of schools and the disruption of daily routine) could negatively affect children’s mental health (Trumello et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 pandemic has strongly influenced people's life (Armour et al, 2021;Babore et al, 2021Babore et al, , 2021bMorelli et al, 2021b;Pistella et al, 2022;Trumello et al, 2021) and sexual behaviors (Bianchi et al, 2021a;Döring, 2020;Eleuteri & Terzitta, 2021). Together and successively with the stay-at-home laws, public health institutions proclaimed the need to avoid physical and sexual contact, suggesting online sexual activities as a safer way to contrast COVID-19 contagion (e.g., International Society for the Study of Women's Sexual Health, 2020).…”
Section: Sexting and Covid-19 Pandemicmentioning
confidence: 99%